2018
DOI: 10.1002/jor.24056
|View full text |Cite
|
Sign up to set email alerts
|

Walking gait asymmetries 6 months following anterior cruciate ligament reconstruction predict 12‐month patient‐reported outcomes

Abstract: The study sought to determine the association between gait biomechanics (vertical ground reaction force [vGRF], vGRF loading rate [vGRF-LR]) collected 6 months following anterior cruciate ligament reconstruction (ACLR) with patient-reported outcomes at 12 months following ACLR. Walking gait biomechanics and all subsections of the Knee Injury and Osteoarthritis Outcomes Score (KOOS) were collected at 6 and 12 months following ACLR, respectively, in 25 individuals with a unilateral ACLR. Peak vGRF and peak insta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 48 publications
(55 citation statements)
references
References 45 publications
1
51
3
Order By: Relevance
“…For example, Hartigan et al reported that a lower external knee flexion moment during gait was a significant predictor of failing a functional return‐to‐sport test battery (quadriceps strength, single‐legged hop tests, and subjective knee function) at 6 months after ACL reconstruction 19 . Pietrosimone et al 20 reported that individuals who walk with lower vertical ground reaction forces compared with their uninjured limb at 6 months after ACL reconstruction present with lower scores on the Knee injury and Osteoarthritis Outcome Score (KOOS) at 12 months after surgery. A secondary purpose was to compare knee extensor and flexor muscle forces during gait between individuals treated with operative compared with nonoperative management at 5 years after ACL injury.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Hartigan et al reported that a lower external knee flexion moment during gait was a significant predictor of failing a functional return‐to‐sport test battery (quadriceps strength, single‐legged hop tests, and subjective knee function) at 6 months after ACL reconstruction 19 . Pietrosimone et al 20 reported that individuals who walk with lower vertical ground reaction forces compared with their uninjured limb at 6 months after ACL reconstruction present with lower scores on the Knee injury and Osteoarthritis Outcome Score (KOOS) at 12 months after surgery. A secondary purpose was to compare knee extensor and flexor muscle forces during gait between individuals treated with operative compared with nonoperative management at 5 years after ACL injury.…”
Section: Introductionmentioning
confidence: 99%
“…These results suggest a fundamental limitation of physical activity indices for monitoring rehabilitation progression. The vast majority of research investigating pathological biomechanics characteristic of gait following ACL-R suggests the existence of more sensitive metrics including quadriceps activation 43 , ground reaction force 33 , and joint work 34 . However, these metrics currently require laboratory-based methodologies that are not widely transferable to clinical use.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research suggests that altered gait biomechanics following ACL-R are responsible for this phenomenon 31,32 . Pathological gait is often characterized by inter-limb asymmetries which manifest early in the post-surgical period 3335 , and develop into compensatory gait patterns over time 11,36 . It is imperative that these maladaptations are identified early so that corrective rehabilitative interventions can be pursued 37 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Greater loading of the ACLR limb has been demonstrated during gait compared with the contralateral limb 139 and the limbs of uninjured control participants. 140 Conversely, others have observed less loading of the ACLR limb during gait, and this reduced loading was associated with greater biochemical markers of inflammation 141 and cartilage breakdown, 142 altered cartilage composition, 143 worse patient-reported outcomes, 144 thinner tibiofemoral cartilage, 145 and radiographic knee OA 5 years after ACLR. 146 The mechanisms leading to abnormal amounts of more or less loading during gait after ACLR are not clear, but data presented at the retreat helped to shed light on potential mechanisms and stimulate directions for future research.…”
Section: Impaired Neuromuscular and Biomechanical Function Postinjurymentioning
confidence: 99%